Thirdhand smoke: Genotoxicity and carcinogenic potential - Bo Hang (KeAi Communications Co., Ltd., 2020)
Thirdhand smoke (THS), the residual tobacco smoke remaining in the environment after tobacco has been smoked, represents a hidden and underestimated public health hazard. Evidence supports its widespread presence in indoor environments. Exposure to secondhand smoke (SHS), a precursor of THS, has been well documented as a risk factor for human cancers, especially lung cancer. However, the concept of THS as a distinct entity that poses health risks for small children has developed only recently and the associations of THS with cancer risk and other chronic diseases are poorly understood due to limited numbers of studies to date. In this perspective, we mainly summarize all published studies on the genotoxicity and carcinogenic potential of THS exposure. These studies begin to fill the knowledge gap in our understanding of cancer risk of THS. Accumulating data from existing and future studies will help reduce the tobacco-related cancer incidence through changes in lifestyle and tobacco control policies. Keywords: Tobacco, Thirdhand smoke, Tobacco-specific nitrosamines, Genotoxicity, Carcinogenesis